Foreign market entry strategy for a Czech manufacturer - Makarova, Yuliia; Semenenko, Vadim; Procházka, Petr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This master’s thesis aims to identify a suitable foreign market for the Czech manufacturing company ZEBR s.r.o. to enter, recommend an optimal mode of entry, and develop a comprehensive marketing strategy tailored to the selected market. The theoretical part provides an overview of internationalization, including motivations, risks, and challenges faced by SMEs, as well as entry modes, strategic tools, and marketing frameworks. The practical part focuses on introducing ZEBR s.r.o., selecting the market using a scoring model, and evaluating the market through PESTEL analysis, Porter’s Five Forces, along with SWOT analysis, and competition analysis. The thesis concludes with a tailored market entry strategy and marketing mix.
Vedoucí práce: Vadim Semenenko
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses